Peran Disperindag Kota Solok dalam Memberdayakan Usaha Mikro Kecil Menengah (UMKM) di Kota Solok pada Masa Pandemi Covid-19 - Herlin Cahya Erwinda; Adil Mubarak (Policy, Law and Political Research Center, 2022)
This research departs from the number of MSMEs in Solok City that have fallen and experienced a decline in income due to the Covid-19 pandemic in Solok City. This type of research is qualitative with a descriptive procedure. In this research, the writer uses the procedure and purposive sampling method. The results of this research are 1. The Role of Disperindag in Efforts to Develop Micro, Small and Medium Enterprises in Solok City during the Covid-19 Pandemic, namely a. The Role of the Solok City Disperindag as a Facilitator, 1) The Solok City Disperindag Role through Trainings, 2) The Solok City Disperindag Role by Finding Capital Assistance for MSME Actors, 3) The Disperindag Role in Marketing MSME Products in Solok City b. The role of the Solok City of Industry and Trade as a Facilitator, namely 1) Solok City's Disperindag role in the decision-making process, 2) Solok City's Industry and Trade Department's role in the regulation of the granting of trademark rights to MSME actors. Guidance, 2) The Role of Disperindag Solok City by Providing Mentoring 2. Supporting Factors, a. Internal factors and b. External Factors, namely 3. Inhibiting Factors a. Internal factors and b. External Factors